Оптимізація замкнених еколого-біотехнічних систем у тваринництві - Чміль, А. І. (Енергетика і автоматика, 2017)
ECOLOGICAL AND OPTIMIZATION closed biotechnological systems in livestock A. Chmil The relationship between man and nature during production sharply UIC-ladnyuyutsya. Continuously increasing metabolism and energy-lyayetsya expression in the expanded use of natural resources and increasing rynnytskyh-ment and other wastes that are returned to the environment, dramatically enhances the overall performance of agricultural production on nature. The ability of the same nature to play intensively used natural resources and self-cleaning of contamination is limited. Therefore, the problem of environmental pollution prevention livestock waste determines need for a closed ecological and biotechnical systems (ZEBS) as an environmentally closed production structures that can "fit" in the equilibrium system environment with minimal losses for her. Based on environmental, energy and sanitary and veterinary requirements developed an integrated energy-saving and environmental protection technology of recycling organic matter livestock farms and poultry farms. The purpose of research - optimization model of energy saving and ecologically safe technologies of processing and disposal of animal waste. Materials and methods of research. The essence of the integrated system is combined bioconversion of organic waste in three stages, by passing the waste of one process module to another for which wastes used as raw materials in order to obtain fertilizer, feed and fuel, intensifying the process of biodegradation, full utilization of mineral substances in the waste, environmental protection and the prevention of the spread of epidemics. Results. Suppose there is some set of animal waste Oh, belonging to different species of animals and birds, which determine the choice of appropriate processing and recycling and implemented on a set of production lines TL, consisting of variations of the same technology or other technologies. You must define a subset of products and waste that can be used in agriculture and other sectors of the economy. Formally, the problem can be formulated as follows: is the set O animal waste and set T technologies that handle O, resulting in the formation of the set PR products and set S waste that meets the set G restrictions. Restrictions are wastes (O_I, ...,O_n) ∈0, which can be processed by a certain set of (T_1, ..., T_n) ∈ T technologies to obtain (PR〗〖_I, ..., PR〗〖_n ) ∈ PR and products (S_1, ..., S_l) ∈ S waste. The set O is considered as input parameter and set PR and S - weekend. G is a fixed set of managed operations, beyond which the system becomes unstable (unmanageable). The problem of determining the vector (T_1, ..., T_n) control actions that generates vector S, whose elements belong to the set O subject G restrictions. Conclusions The results of the solution of the problem is the basis for adjusting the process parameters that will change the output performance of products in established regulatory limits. In the resulting waste of some enterprises for its quality indicators will be closer to the main raw material of other companies.